A genetic switch : phage [lambda] and higher organisms - Ptashne, Mark. (Cambridge, Mass. : Blackwell Scientific pub. & Cell press, 1992)
The master elements of control; Protein-DNA interactions and gene control; Control circuits - setting the switch; How do we know - the key experiments; Eukaryotic gene regulation - an overview; Eukaryotic gene regulation - experiments and examples.
On t.p. lambda in shown as symbol following phage.
Includes bibliographical references and index.
Keywords: Genetic regulation; Genetic regulation; Bacteriophage lambda; Viral genetics